2021
DOI: 10.3390/antiox10091434
|View full text |Cite
|
Sign up to set email alerts
|

2-Oxo-Imidazole-Containing Dipeptides Play a Key Role in the Antioxidant Capacity of Imidazole-Containing Dipeptides

Abstract: There is substantial evidence for the antioxidant functions of imidazole-containing dipeptides (IDPs), including carnosine and anserine, under physiological and pathological conditions in vivo. However, the detailed mechanism underlying the antioxidant functions is still poorly understood. Recently, we discovered the endogenous production of 2-oxo-imidazole-containing dipeptides (2-oxo-IDPs), such as 2-oxo-carnosine and 2-oxo-anserine, as novel derivatives of IDPs in mouse tissues and revealed that the antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…However, no study has used isotope-labeled balenine. The application of HPLC-ESI-MS/MS coupled with a stable isotope dilution method for 2-oxo-IDPs has only been demonstrated by our previous reports for the detection of 2-oxo-carnosine [ 7 , 24 , 25 ], 2-oxo-anserine [ 7 , 24 , 25 ], 2-oxo-homocarnosine [ 7 ], and 2-oxo-homoanserine [ 23 ]. However, no study has demonstrated about 2-oxo-balenine.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, no study has used isotope-labeled balenine. The application of HPLC-ESI-MS/MS coupled with a stable isotope dilution method for 2-oxo-IDPs has only been demonstrated by our previous reports for the detection of 2-oxo-carnosine [ 7 , 24 , 25 ], 2-oxo-anserine [ 7 , 24 , 25 ], 2-oxo-homocarnosine [ 7 ], and 2-oxo-homoanserine [ 23 ]. However, no study has demonstrated about 2-oxo-balenine.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that 2-oxo-IDPs (i.e., 2-oxo-carnosine, 2-oxo-anserine, and 2-oxo-homoanserine) exhibit a greater antioxidant capacity, compared to the corresponding IDPs [ 7 , 23 , 25 ]. Further, it has been reported that 2-oxo-carnosine shows significant cytoprotective effects on rotenone-induced neuronal cell death, while there are no significant effects by the treatment with the precursor carnosine [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations